2014
DOI: 10.1016/j.ijhydene.2014.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sorption hysteresis and superior storage capacity of silicon-carbide nanotubes over their carbon counterparts

Abstract: We report for the first time the results of an extensive experimental study of hydrogen sorption in silicon-carbide nanotubes (SiCNTs), which were synthesized using the reaction between SiO vapor and carbon nanotubes (CNTs) in an argon atmosphere in the temperature range 1200 o C-1500 o C. The as-synthesized SiCNTs were then purified using a sodium hydroxide solution in order to remove the side products of the synthesis reaction. The hydrogen sorption characteristics of the as-synthesized SiCNTs, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…According to the equation, the specific capacitance of CuS hollow spheres is calculated to be 917.6 F g À1 compared to 2317.8 F g À1 of CuS-rGO composite. This value of CuS-rGO composite is higher than that for flower-like CuS synthesized in glycerol (597 F g À1 ) and measured in aqueous 2 M KOH solution [41], CuS nanoplatelets fabricated by low temperature chemical bath deposition technique (72.85 F g À1 ) and measured in 1 M H 2 SO 4 aqueous electrolyte [42], CuS ultrafine nanoneedles supported on a carbon nanotube backbone fabricated by an efficient template-engaged chemical conversion route (114 F g À1 ) and measured in 2 M aqueous KOH solution [23], CuS microspheres with polypyrrole uniformly inserted into the sheet like subunit structure (427 F g À1 ) and measured in the electrolyte of 1 M KCl [24].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…According to the equation, the specific capacitance of CuS hollow spheres is calculated to be 917.6 F g À1 compared to 2317.8 F g À1 of CuS-rGO composite. This value of CuS-rGO composite is higher than that for flower-like CuS synthesized in glycerol (597 F g À1 ) and measured in aqueous 2 M KOH solution [41], CuS nanoplatelets fabricated by low temperature chemical bath deposition technique (72.85 F g À1 ) and measured in 1 M H 2 SO 4 aqueous electrolyte [42], CuS ultrafine nanoneedles supported on a carbon nanotube backbone fabricated by an efficient template-engaged chemical conversion route (114 F g À1 ) and measured in 2 M aqueous KOH solution [23], CuS microspheres with polypyrrole uniformly inserted into the sheet like subunit structure (427 F g À1 ) and measured in the electrolyte of 1 M KCl [24].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…After the degasing step was completed, the system's temperature was set to the value at which gas absorption was to be investigated, in this study in the range 25 Ce55 C. The system pressure was then increased stepwise by injecting the absorptive gas into the gravimetric vessel, and the sample's weight was recorded. More details about the experimental set-up used in this work and the operating procedures followed are given in our previous papers [28,29]. Fig.…”
Section: Gas Absorption Measurementsmentioning
confidence: 99%
“…In our previous studies of the adsorption of hydrogen in carbon and silicon-carbide nanotubes [28,29], we utilized a highly accurate gravimetric measurement technique involving the use of a magnetic suspension microbalance. A key goal of the present paper is to extend the applicability of this technique as a viable experimental tool to simultaneously measure the solubility and diffusivity of various gases in ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest proof of chemisorption in carbon nanotubes is the requirement of high temperature to completely remove hydrogen from hydrogenated CNTs [55]. Although it has been reported that the hysteresis phenomenon between the adsorption/desorption isotherms of CNTs can also suggest the chemisorption [12], Barghi et al [66] attributed hysteresis to the metal impurities formed during CNT synthesis and/or the multilayer structure of the CNTs.…”
Section: Introductionmentioning
confidence: 99%